Academic Resilience of Higher Secondary School Students of District Srinagar - Mudassir Yousuf Naik; Shahed Hussain; Aaqib Farooq Sheikh (CV. Radja Publika, 2026)
Academic resilience is increasingly viewed as a key factor in student’s ability to manage academic challenges and sustain performance. This study examines the level of academic resilience among higher secondary school students of Srinagar, with particular reference to gender and type of school. Using a quantitative research design, a sample of 200 student’s (107 males and 93 females) was selected through simple random sampling from government and private schools. Data were collected using the Academic Resilience Scale (ARS-MMKS, 2016) and analysed through descriptive statistics and t-test. The findings indicate that most students demonstrate moderate resilience, while a notable proportion exhibits lower levels, suggesting the need for targeted support. Significant differences were observed based on gender (p = 0.001), with males showing higher resilience and school type (p = 0.025), with private school students outperforming those in government schools. The study highlights the role of socio-institutional factors and emphasizes the need for context-specific, gender-sensitive strategies to strengthen student’s adaptive capacities in academic settings.